Formalizing the Informal: Development and its Impacts on Traditional Dispute Resolution in Bhutan - Stephan Sonnenberg (Washington University Journal of Law & Policy, 2020)
Bhutan, a small landlocked country, with less than a million residents lies between two of the most populous nations on earth, India and China. Beyond its beautiful scenery and national development philosophy of pursuing “Gross National Happiness,” this Article argues that it should also be known for its heritage of traditional dispute resolution. This system kept peace in villages for centuries; however, now such tradition face extinction. As argued below, such extinction stems from modernization. This Article explores the interplay between reforms to the formal justice system and the informal dispute resolution practices that operate at the local level, as well as the way these changes impact rural communities. Further, it raises important ethical questions about development initiatives that are aimed at promoting the rule of law, especially when it comes to informal, or so-called “alternative” dispute resolution processes in pluralistic legal systems.
Keywords: Bhutan; traditional dispute resolution; dispute resolution; alternative dispute resolution; ADR